2019
DOI: 10.5539/ijel.v9n5p52
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Impact Factors Influencing Students’ Reading Literacy in Singapore with Machine Learning Approaches

Abstract: This study identified the contextual factors which differentiated 15-year-old students with high- and low-achieving reading literacy in Singapore based on Program for International Student Assessment (PISA) 2015. 4,015 students from Singapore were collected from the public dataset of PISA 2015, with 2,646 high-achieving students and 1,369 low-achieving students in PISA reading literacy test. The impact of the overall 49 contextual factors on reading literacy was analyzed in three levels: student level, family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 65 publications
3
19
0
1
Order By: Relevance
“…The PISA 2018 assessment does not provide actual reading achievement scores for each student; instead, it measures proficiency in each domain using ten plausible values that represent ten random values drawn from the posterior distribution of the student's scores for reading [6]. We used the first plausible value for the overall reading proficiency; previous studies on the PISA dataset have used only one plausible value [8,9,45] based on the assumption that one plausible value is said to provide unbiased estimates of population parameters. The distribution of students based on their reading level and group is summarized in Figure 2, which also shows that 55% and 45% of the students belonged to the low and high performing groups, respectively.…”
Section: The Datasetmentioning
confidence: 99%
“…The PISA 2018 assessment does not provide actual reading achievement scores for each student; instead, it measures proficiency in each domain using ten plausible values that represent ten random values drawn from the posterior distribution of the student's scores for reading [6]. We used the first plausible value for the overall reading proficiency; previous studies on the PISA dataset have used only one plausible value [8,9,45] based on the assumption that one plausible value is said to provide unbiased estimates of population parameters. The distribution of students based on their reading level and group is summarized in Figure 2, which also shows that 55% and 45% of the students belonged to the low and high performing groups, respectively.…”
Section: The Datasetmentioning
confidence: 99%
“…The performance of models with more than 20 is negatively influenced. Second, SVM-based studies in the social sciences have identified 20 to 30 features as a good number for an optimal feature set [ 108 ], and 20 features were selected for inclusion in the optimal feature set [ 95 ]. Therefore, in this study, the top 20 features were selected for subsequent analysis, as proposed in previous analyses that yielded accepted measurement rates.…”
Section: Resultsmentioning
confidence: 99%
“…The SVM contains the following two modules: one module is a general-purpose machine learning method, and the other module is a domain-specific kernel function. The SVM training algorithm is used to build a training model that is then used to predict the category to which a new sample instance belongs [ 95 ]. When a set of training samples is given, each sample is given the label of one of two categories.…”
Section: Methodsmentioning
confidence: 99%
“…Pese al eclecticismo de las comunidades mencionadas, la tendencia más común se vincula a que en el modelo tradicional, en el que el docente instruye y al alumnado adquiere los contenidos de forma pasiva, los resultados se caracterizaron por un lado, por la escasa influencia y relación entre las variables y, por otro, por una gran dispersión entre las mismas. Este hallazgo se contrapone a la mayoría de la literatura vinculada a la temática objeto de estudio en la que, en la mayoría de casuísticas, la utilización de modelos y métodos tradicionales se asocia a un mayor rendimiento académico del alumnado en PISA lectura (Dong & Hu, 2019;Giménez, Barrado & Arias, 2019;Gubbels et al, 2020;Perera & Asadullah, 2019;Torrpa, Eklund, Sulkunen, Niemi & Ahonen, 2017).…”
Section: Discusión Y Conclusionesunclassified